Organic cultivation and deficit irrigation practices to improve chemical and biological activity of mentha spicata plants - Chrysargyris, Antonios; Koutsoumpeli, Eleni; Xylia, Panayiota; Fytrou, Anastasia; Konstantopoulou, Maria; Tzortzakis, Nikos G. (My University, 2021)
Intensive crop production and irrational use of fertilizers and agrochemicals have ques-tionable effects on the quality of products and the sustainable use of water for agricultural purposes. Organic cultivation and/or deficit irrigation are, among others, well appreciated practices for a sustainable crop production system. In the present study, spearmint plants (Mentha spicata L.) were grown in different cultivation schemes (conventional versus organic cultivation, full versus deficit irrigation), and effects on the plant physiological and biochemical attributes were examined in two harvesting periods. Deficit irrigation decreased plant growth, but increased total phenolics, flavonoids, and antioxidant capacity of the plants at the second harvest. Spearmint nutrient accumulation was affected by the examined cultivation practices; nitrogen was decreased in organic cultivation, potassium and sodium were elevated at full-irrigated plants, while magnesium, phosphorus, and copper levels were higher at the deficit-irrigated plants. However, conventional/full-irrigated plants had increased height and fresh biomass at the first harvest. Essential oil content decreased at the second harvest in organic and/or deficit treated plants. Additionally, deficit irrigation affected plant growth and delayed the formation of carvone from limonene. The essential oils were further evalu-ated with regard to their bioactivity on a major vineyard pest Lobesia botrana. Volatile compounds from all essential oils elicited strong electroantennographic responses on female insects antennae, highlighting the role of carvone, which is the major constituent (~70%) in all the tested essential oils. M. spicata essential oils also exhibited larvicidal activity on L. botrana, suggesting the potential of their incorporation in integrated pest management systems.
Keywords: Spearmint; Medicinal and aromatic plants; Sustained deficit irrigation; Insecticidal activity; Antioxidant activity; Electroantenographic response